Headspace solid-phase microextraction for the evaluation of pesticide residue contents in cucumber and strawberry after washing treatment - Chai, M.K.; Tan, G.H. (Elsevier, 2010)
The headspace solid-phase microextraction was developed to examine the organophosphorus (diazinon, malathion, chloropyrifos, quinalphos, profenofos) and organochlorine (chlorothalonil, alpha-endosulfan and beta-endosulfan) pesticide residues in vegetable (cucumber) and fruit (strawberry) samples. The effects of washing by different solutions were evaluated for the reduction of organophosphorus and organochlorine pesticide residues contents. Gas chromatography with electron capture detection was used to analysis the investigated pesticides. The results showed that washing by a non-toxic solution can decrease the concentration of pesticide residues in the fruit and vegetable samples. The data further indicated that acetic acid was the most effective solution in removing the residues of the investigated pesticides from the fruit and vegetable samples when compared to sodium carbonate, sodium chloride and tap water. The amount of pesticides removed by solution washing is related to their water solubility and vapour pressure properties. (C) 2010 Elsevier Ltd. All rights reserved.